Auditory function in the Tc1 mouse model of down syndrome suggests a limited region of human chromosome 21 involved in otitis media. - Stephanie Kuhn; Neil Ingham; Selina Pearson; Susan M Gribble; Stephen Clayton; Karen P Steel; Walter Marcotti (PLoS ONE)
Down syndrome is one of the most common congenital disorders leading to a wide range of health problems in humans, including frequent otitis media. The Tc1 mouse carries a significant part of human chromosome 21 (Hsa21) in addition to the full set of mouse chromosomes and shares many phenotypes observed in humans affected by Down syndrome with trisomy of chromosome 21. However, it is unknown whether Tc1 mice exhibit a hearing phenotype and might thus represent a good model for understanding the hearing loss that is common in Down syndrome. In this study we carried out a structural and functional assessment of hearing in Tc1 mice. Auditory brainstem response (ABR) measurements in Tc1 mice showed normal thresholds compared to littermate controls and ABR waveform latencies and amplitudes were equivalent to controls. The gross anatomy of the middle and inner ears was also similar between Tc1 and control mice. The physiological properties of cochlear sensory receptors (inner and outer hair cells: IHCs and OHCs) were investigated using single-cell patch clamp recordings from the acutely dissected cochleae. Adult Tc1 IHCs exhibited normal resting membrane potentials and expressed all K(+) currents characteristic of control hair cells. However, the size of the large conductance (BK) Ca(2+) activated K(+) current (I(K,f)), which enables rapid voltage responses essential for accurate sound encoding, was increased in Tc1 IHCs. All physiological properties investigated in OHCs were indistinguishable between the two genotypes. The normal functional hearing and the gross structural anatomy of the middle and inner ears in the Tc1 mouse contrast to that observed in the Ts65Dn model of Down syndrome which shows otitis media. Genes that are trisomic in Ts65Dn but disomic in Tc1 may predispose to otitis media when an additional copy is active.